An Exactly Soluble Equation for the Stationary Probability Distribution in a Nonlinear System under the Influence of Two-telegraph Noise: Application to the Noise Reduction in a Raman Ring Laser - Khoa, Doan Quoc; Lanh, Chu Van; Sanh, Phan Xuan; Sang, Nguyen Thi Hong; Hoa, Le Thi; Thu, Nguyen Thi; Dung, Bui Van (Communications in Physics, 2016)
In this paper, we will consider a model of nonlinear system with random telegraph noises and a Raman ring laser by modeling the laser pump light by a pregaussian process and find an exactly soluble equations for the stationary probability distribution of fluctuations in this nonlinear system under the influence of two-telegraph noise. In consequence, we will obtain the so-called noise reduction in this system: the Stokes output of this laser tends to the stabilize under the influence of the broad-band two-telegraph pregaussian pump and compare this results with that obtained in our previous paper (Cao Long Van, Doan Quoc Khoa, Opt. Quant. Electron. 43, 137 (2012)) for the case of one telegraph noise.